The effect of parent administered infant massage on the developmental milestones of premature infants - Perrie, Megan (My University, 2019)
Prematurely born infants have been shown to have developmental delays in multiple areas when compared to infants who were born at term (Formiga & Linhares, 2010) (Guerra, et al., 2014). This study investigated the developmental milestones of infants who had and had not received parent-administered infant massage for the first four to six months of their lives. The Peabody Developmental Motor Scales Second Edition (PDMS-2) test was carried out on infants at birth and then again at four to six months actual age along with the Bayley Scales of Infant and Toddler Development Third Edition (BSID-III). Positive clinical effect sizes were shown in the massaged group in the Cognitive, Reflexes and Visual-Motor Integration sub-tests. There was also a strong correlation between frequency of massage and social-emotional development of the massaged infants. Larger scale research is still required to confirm the findings of this study.
A dissertation submitted to the Faculty of Health Sciences, School of Therapeutic Sciences, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements of the degree of Master of Science in Occupational Therapy Johannesburg 2019
Keywords: Massage--in infancy & childhood; Infant, Premature; Pediatrics